Reprentasi identintas budaya dalam sastra postkolonial - Nisa, Qurrota Ainin (Maliki Interdisciplinary Journal, 2025)
This study on the depiction of cultural identity in postcolonial cultures focuses on the production, negotiation, and deconstruction of post-colonial identities as its primary areas of investigation. Through the use of the postcolonial methodology proposed by Homi K. Bhabha, Stuart Hall, and Edward Said, this study analyzes the ways in which components of local culture are represented in connection to colonial power. The primary sources of information are the works of Chinua Achebe's Things Fall Apart, Salman Rushdie's Midnight's Children, Arundhati Roy's The God of Small Things, and Season of Migration to the North. Specifically, the descriptive qualitative technique was implemented through the utilization of the close reading method and critical discourse analysis. According to the findings, the cultural identity that is shown in postcolonial novels is not only fluid and hybrid, but it is also the outcome of a complicated struggle between modernity and tradition. Furthermore, the findings of this research indicate that depictions of cultural identity in postcolonial literature are frequently ambiguous and problematic. This finding lends credence to the notion that colonialism continues to exert an influence on postcolonial communities.